2012
DOI: 10.1681/asn.2012030302
|View full text |Cite
|
Sign up to set email alerts
|

Circulating suPAR in Two Cohorts of Primary FSGS

Abstract: Overexpression of soluble urokinase receptor (suPAR) causes pathology in animal models similar to primary FSGS, and one recent study demonstrated elevated levels of serum suPAR in patients with the disease. Here, we analyzed circulating suPAR levels in two cohorts of children and adults with biopsyproven primary FSGS: 70 patients from the North America-based FSGS clinical trial (CT) and 94 patients from PodoNet, the Europe-based consortium studying steroid-resistant nephrotic syndrome. Circulating suPAR levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
183
4
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 202 publications
(207 citation statements)
references
References 33 publications
15
183
4
3
Order By: Relevance
“…We confirmed these findings in patients with FSGS from two well characterized cohorts: the FSGS Clinical Trial (FSGS CT) (n570, pediatric and adult patients, eGFR .40 ml/min per 1.73 m 2 ) and the PodoNet European FSGS consortium (n594, pediatric patients, normal eGFR) (8). Using 3 ng/ml as a cut-off value, we demonstrated that suPAR levels were elevated in 84% and 55% of patients in the two cohorts, respectively.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…We confirmed these findings in patients with FSGS from two well characterized cohorts: the FSGS Clinical Trial (FSGS CT) (n570, pediatric and adult patients, eGFR .40 ml/min per 1.73 m 2 ) and the PodoNet European FSGS consortium (n594, pediatric patients, normal eGFR) (8). Using 3 ng/ml as a cut-off value, we demonstrated that suPAR levels were elevated in 84% and 55% of patients in the two cohorts, respectively.…”
supporting
confidence: 69%
“…It should be noted that although the authors assert that they performed the first evaluation of suPAR in pediatric patients with FSGS, 42 of the 70 patients enrolled in the FSGS CT were aged ,18 years and were included in the random subset selected for assay of plasma suPAR levels. Moreover, the PodoNet cohort included children and adolescents with FSGS (8). However, it is worth exploring potential differences that might explain the disparate findings.…”
mentioning
confidence: 99%
“…suPAR-mediated activation of β3 integrin is the putative mechanism of action of this molecule. A follow-up study reported elevated serum suPAR levels in 55 and 84 % of patients with primary FSGS in two welldescribed cohorts compared to 6 % of controls [38]. Elevated levels of suPAR were noted in patients with an NPHS2 mutation.…”
Section: Pathogenesismentioning
confidence: 97%
“…Elevated levels of suPAR were noted in patients with an NPHS2 mutation. In addition, lower levels were associated with male sex and increased estimated GFR [38]. Findings in other cohorts have raised questions about the role of suPAR in the pathogenesis of proteinuria, its ability to discriminate FSGS from other forms of primary glomerular disease, and its predictive value in identifying recurrent disease post-transplant [39][40][41].…”
Section: Pathogenesismentioning
confidence: 99%
“…Several follow-up studies confirmed increased total suPAR serum levels in FSGS, which were validated in patients with normal or mildly reduced renal function compared with other glomerular diseases 5 but not necessarily in advanced renal failure in which suPAR accumulation may occur. 6 Furthermore, it should be noted that in certain recent studies, serum suPAR did not differentiate FSGS from other glomerulopathies in the setting of relatively preserved renal function.…”
mentioning
confidence: 82%